Predicting the success of induction of labour using cervical volume - Malitha Patabendige; Sanka Rajesh Athulathmudali (BMC Research Notes, 2021)
Abstract Objectives Assessing the likelihood of success of induction of labour using cervical volume is an important research question. Data description We provide data generated in a prospective observational study which was carried out at North Colombo Teaching Hospital, Ragama, Sri Lanka. Study conducted to compare pre-induction digital cervical assessment, sonographic cervical length, and sonographic cervical volume with vaginal delivery rate within 24 h. Inductions with 100 singleton pregnancies at term were included.